SOME STUDIED DATA ON THE CURRENT STATUS OF MANGROVE ECOSYSTEM IN PHU LONG (CAT HAI - HAIPHONG) - Huyen, Nguyen Thi Minh; Thu, Nguyen Thi; Hao, Do Manh; Thanh, Le Thi; Quan, Do Van (Vietnam Journal of Marine Science and Technology, 2014)
In the framework of project "Study and appli-cation methods to evaluate the natural resource economy for some typical ecosystems in Haiphong coastal area, and propose the solutions for the sustainable use", the study of evaluation on the state of mangrove ecosystems in Phu Long (Cat Hai district, Hai Phong City) were implemented to provide the scientific basis for identifying and quantifying the ecological values monetized into currency. This article contributes to provide scientific data on the state of the mangrove ecosystem in Phu Long, which has been investigated by scientific collective of the Institute of Marine Environment and Resources from 2008 - 2009. Research results showed that mangrove eco-system in Phu Long is high in biodiversity, has decreased greatly  in area, and declined strongly in the ecosystem’s  quality. The aquatic resources have been in signs of depletion, that shown by changes in sources of the shrimp and fish larvae, and catching production. Recently, the local government has been implimented promptly and efficiently management policies for mangrove forest.